Shifting Perspectives in Tribal Studies From an Anthropological Approach to Interdisciplinarity and Consilience - Behera, Maguni Charan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book brings together multidisciplinarity, desirability and possibility of consilience of borderline studies which are topically diverse and methodologically innovative. It includes contemporary tribal issues within anthropology and other disciplines. In addition, the chapters underline the analytical sophistication, theoretical soundness and empirical grounding in the area of emerging core perspectives in tribal studies. The volume alludes to the emergence of tribal studies as an independent academic discipline of its own rights. It offers the opportunity to consider the entire intellectual enterprise of understanding disciplinary and interdisciplinary dualism, to move beyond interdisciplinarity of the science-humanities divide and to conceptualise a core of theoretical perspectives in tribal studies. The book proves an indispensable reference point for those interested in studying tribes in general and who are engaged in the process of developing tribal studies as a discipline in particular. .
Chapter 1 Rethinking Perspectives in Tribal Studies: Anthropology and Beyond Maguni Charan Behera -- Part I Indigenous Dilemma -- Chapter 2 Culture: the Indigenous Account Alan Barnard -- Chapter 3 Confluence of Hindutva Protagonists and Indigenous Religious Reform Movements in North East India Soihiamlung Dangmei -- Chapter 4 Indigenous Knowledge and Value Systems in India: Holistic Analysis of Tribal Education and the Challenge of Decentralising Control Malvika Gupta and Felix Padel -- Part II Inter-Community Space -- Chapter 5 Rajas, Adibasis and their Goddess (es): Dasara rituals and a sacrificial polity in a former feudatory state in Odisha Uwe Skoda -- Part III Contextual Analysis (Case-based Studies) -- Chapter 6 Participation of South Odishan Tribes in Naxal Movements: A Contextual Analysis K. Anuradha and Jagannath Dash -- Chapter 7 Politics of Maoism, Adivasi Human Rights Issues and the State: A Study of Chhattisgarh Rajesh Kumar Meher -- Chapter 8 Environmental Illness at Klity Creek (Thailand): A Karen Village's Quest for Justice Malee Sitthikriengkrai and Nathan Porath -- Chapter 9 Rallying around Sacred Natural Sites: Adivasi Mobilisations in East-Central India Radhika Borde -- Part IV Space of Convergence -- Chapter 10 Non-Timber Forest Products (NTFPs) and Livelihood Promotion of Tribes of Odisha S. N. Tripathy -- Chapter 11 A Content Analysis of Education amongst the Scheduled Tribes in Jharkhand: Emphasising Government's Perspective & Conscientiousness Binod Narayan & Utpal Kumar Chakraborty -- Chapter 12 Documentation and Digitisation for Access to Traditional Medicine Knowledge in Southern Odisha Rashmi Pramanik -- Chapter 13 Land, property rights and management issues in tribal areas of Jharkhand: An overview Hari Charan Behera -- Chapter 14 Mining and Anthropology in Indian Industrialism Rajanikant Pandey -- Part V Embryonic Synthesis -- Chapter 15 Epidemiology of Blood Pressure among the Tribes of Odisha Kanhu Charan Satapathy, Prasanna Kumar Patra and Shyama Mohapatra -- Chapter 16 Mother Care among Some Bathudi Tribal Women in Simlipal Reserve Forest Area in Eastern India Sutapa Mukhopadhyay and Ranjana Ray -- Part VI Borderline Interdisciplinarity -- Chapter 17 Local knowledge in managing upland agriculture by the Adis in Arunachal Pradesh, North East India Prasanna K. Samal, Rajiv Mili & Mihin Dollo -- Chapter 18 Tribal Philosophy: An Epistemological Understanding of Tribal Worldview Heni Francis Ariina.
Keywords: Anthropology; Ethnology; Culture -- Study and teaching; Anthropology; Sociocultural Anthropology; Cultural Studies